Repair of Pharyngocutaneous Fistula (PCF) Using Montgomery Salivary bypass Tube after Salvage Total Laryngectomy following Failed Primary Radiotherapy: A Case Report - Mohd Sayuti, Razali; Nor Kamaruzaman, Esa; Salman, Amiruddin; Syaratul Emma, Hashim (2018)
The occurrence of pharyngocutaneous fistula (PCF) after total salvage laryngectomy following radiotherapy as primary treatment is quite common. In most cases, pharyngocutaneous fistula can heal spontaneously with conservative measures. Here, we are reporting a 69-year-old male with a residual carcinoma of the larynx following failed radiotherapy as primary treatment whose later underwent a salvage total laryngectomy. Post-operatively, it was complicated by the formation of pharyngocutaneous fistula which was failed to heal with conservative measures and few attempts of surgical repair. The fistula later healed with the application of Montgomery Salivarybypass tube after 3 weeks. The application of the salivary bypass tube should be considered and used to promote healing in persistent pharyngocutaneous fistula especially in a post radiotherapy patient.